M-current and its role in neuronal physiology - Brown, David A. (Henry Stewart Talks, 2011)
Basic properties, Molecular composition, Inhibition by acetycholine and mechanism of inhibition, Functions: membrane potential clamp, Control of action potential discharges, Control of nociceptive sensory excitation, Suppression of repetitive discharges at nodes of Ranvier, Regulation of action potential threshold at axon initial segment, Suppression of epileptiform discharges in central neurons, Contribution of M-channel inhibition to cholinergic excitation
Updated at 2020/05/01